The role of the internet in the process of Muslims radicalization in the Western Balkans - Simonović Branslav; Popović Predrag (NBP: Nauka, bezbednost, policija, 2023)
The research subject of this paper is the video material posted on YouTube in Bosnian and Serbian with the intention to radicalize the Muslim population from the Western Balkans. The analyzed video materials with radical messages were classified into two groups. Ones that aim at changing attitudes (cognitive radicalization) and the ones that propagate change in behaviour (engaging in violence, murder, terrorist acts, etc.). Narratives from those two basic groups were divided into subgroups within which their content was analyzed. The research in this paper showed that extreme Muslim radical messages that lead to terrorism expressed in the languages of small nations (in this case in Serbian or Bosnian) could have not only local, but a global, destructive aims, considering the global danger of Muslim radicalism.